Food systems resource center - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
Food systems in low- and middle-income countries are changing rapidly, with serious consequences for the nutritional health and wellbeing of billions of people. A4NH’s Research Flagship on Food Systems for Healthier Diets provides research and support to countries working to ensure their food systems develop in a way that ensures people have equitable access to nutritious and sustainable diets. The Food Systems Resource Center provides access to research, tools, ideas, and people conducting work in this important area.